Cometary plasma response to interplanetary corotating interaction regions during 2016 June–September: a quantitative study by the Rosetta Plasma Consortium. Issue 4 (9th August 2018) - Hajra, Rajkumar; Henri, Pierre; Myllys, Minna; Héritier, Kevin L; Galand, Marina; Simon Wedlund, Cyril; Breuillard, Hugo; Behar, Etienne; Edberg, Niklas J T; Goetz, Charlotte; Nilsson, Hans; Eriksson, Anders I; et al.
ABSTRACT: Four interplanetary corotating interaction regions (CIRs) were identified during 2016 June–September by the Rosetta Plasma Consortium (RPC) monitoring in situ the plasma environment of the comet 67P/Churyumov–Gerasimenko (67P) at heliocentric distances of ∼3–3.8 au. The CIRs, formed in the interface region between low- and high-speed solar wind streams with speeds of ∼320–400 km s −1 and ∼580–640 km s −1, respectively, are characterized by relative increases in solar wind proton density by factors of ∼13–29, in proton temperature by ∼7–29, and in magnetic field by ∼1–4 with respect to the pre-CIR values. The CIR boundaries are well defined with interplanetary discontinuities. Out of 10 discontinuities, four are determined to be forward waves and five are reverse waves, propagating at ∼5–92 per cent of the magnetosonic speed at angles of ∼20°–87° relative to ambient magnetic field. Only one is identified to be a quasi-parallel forward shock with magnetosonic Mach number of ∼1.48 and shock normal angle of ∼41°. The cometary ionosphere response was monitored by Rosetta from cometocentric distances of ∼4–30 km. A quiet time plasma density map was developed by considering dependences on cometary latitude, longitude, and cometocentric distance of Rosetta observations before and after each of the CIR intervals. The CIRs lead to plasma density enhancements of ∼500–1000 per cent with respect to the quiet time reference level. Ionospheric modelling shows that increased ionization rate due to enhanced ionizing (>12–200 eV) electron impact is the prime cause of the large cometary plasma density enhancements during the CIRs. Plausible origin mechanisms of the cometary ionizing electron enhancements are discussed.